Gender and Social Support for Sports among Vocational Schools Studets in Indonesia - Syah, Nur Rahmad; Rosidi, Sakban; Lani, Ahmad; Sucipto, Adi; Sunuyeko, Nurcholis (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2023)
With the jargon "SMK Bisa", the government has high hopes for vocational schools. However, this hope has not been supported by policies to improve students' physical fitness. This secondary research analyzes gender and social support data from 1,320 vocational school students. Data were analyzed using the t-test technique for a single sample and two independent samples. The results of this research are: social support for sports activities is not yet categorized as good, social support for sports activities for male and female students is not yet categorized as good, there are differences in social support for sports activities for male and female students.